Dynamic analysis of growth characteristics, secondary metabolites accumulation, and an in-depth understanding of anthraquinones biosynthesis in Rubia cordifolia Linn. - Lian, Conglong; Liu, Xiuyu; Guo, Kaihua; Yang, Hao; Yang, Jingfan; Lan, Jinxu; Chen, Suiqing (Frontiers in Plant Science, 2025)
Rubia cordifolia is a well-known plant used in oriental medicine plant, and is also serves as the primary traditional source of plant red dyestuffs. With the current depletion of natural resources of R. cordifolia, it is critical to conduct cultivation studies on the R. cordifolia. Here, we report on the dynamic growth characteristics and secondary metabolite accumulation of cultivated R. cordifolia, as well as the discovery of important genes involved in anthraquinone biosynthesis. The results showed that R. cordifolia grows better in sunny environments than in shaded environments, and its triennials better than its biennials, base on the biomass and the concentration of the primary components purpurin and mollugin. The dynamic accumulation of purpurin and mollugin content suggested that 30 June to 15 October is a fair window for harvesting R. cordifolia, and the possibility of a specific transition connection during the purpurin and mollugin biosynthesis process. Furthermore, we sequenced R. cordifolia using SMRT technology for the first time and obtained 45,925 full-length transcripts, 564 alternative splicing events, 3182 transcription factors, 6454 SSRs, and 6361 lncRNAs. We hypothesized an anthraquinone biosynthetic pathway and found 280 full-length transcripts that may be involved in anthraquinone biosynthesis in R. cordifolia. In addition, RT-qPCR was used to detect the relative expression levels of 12 candidate ungenes in the above- and underground parts of R. cordifolia. Above all, our findings have crucial implications for the field management of cultivation and harvesting of cultivated R. cordifolia, and also provide useful genetic information for clarifying the potential genes involved in anthraquinone biosynthesis.